تأثير تمرينات اثقال الحرة في بعض قابليات البايوحركية لدى لاعبي كرة اليد الشباب - محمد, أ.م.د.هوشيار عبدالرحمن; محمد, مريوان حسن (Sulaimani Journal for Humanities, 2023)
The handball match is one of the team games which is enjoys great popularity at the local and international levels, due to its wonderful combination of technical performance and fast pace, which impresses the audience, especially when scoring goals. Upgrading the level of physical performance depends largely on the development of mobility capabilities as the basis for proper preparation and construction of the player. Therefore, the importance of research lies in the effect of plyometric exercises on some capabilities and accuracy of shooting from high jumping for handball players. The researchers did not find a training curriculum based on a scientific basis that raises the level of bio motor capabilities by the trainers, and they do not express the special importance of the elements, the special motor abilities, and from here the urgent need for this research appeared and its idea in the preparation of exercises, from here the researchers decided to develop a training program using plyometric exercises in some Biomoteor capabilities and shooting accuracy index from high jumping for handball players. Statistically, there are significant differences between the results of the pre- and post-tests of the mobility capabilities and the accuracy index of shooting from the high jump of the handball players. As for the research methodology, the researchers used the experimental approach. They were processed statistically, and the following conclusions were reached: The proposed exercises achieved positive results in developing some mobility capabilities of handball players. The effectiveness of plyometric exercises led to the development of the bio motor capabilities of handball players in the experimental group between the pre- and post-test and in favour of the post test. As for the recommendations: focus on using plyometric exercises during training units for age groups and in the forms that suit them. The administrative bodies in clubs and sports institutions should give sufficient attention for age groups by providing the devices and tools used to implement the training units and everything that the trainer needs.